Older male mentors: Outcomes and perspectives of an intergenerational mentoring program for young adult males with intellectual disability. (1st May 2019) - Mahoney, Natasha; Wilson, Nathan J.; Buchanan, Angus; Milbourn, Ben; Hoey, Ciarain; Cordier, Reinie
Abstract: Issue addressed: Intergenerational mentoring is emerging as a way to provide meaningful engagement and improve wellbeing for older adults in retirement. However, there is little, if any, Australian research concerning the benefits for older mentors involved in such mentoring. This study aims to investigate the experiences of older male mentors involved in an intergenerational mentoring program with young men with intellectual disability and identify any benefits to physical and mental health and generativity. Methods: This study used a mixed methods concurrent triangulation design. Quantitative outcomes data were collected pre and postintervention using the SF‐36 and Loyola Generativity Scale. Qualitative data were collected using a single‐interview approach. Mentors and mentees took part in a 6‐month mentoring program based in Australian Men's Sheds. Results: No significant changes were seen in physical health and generativity. Investigation of mental health scores revealed a significant improvement in scores on the mental health subscale. Qualitative analysis revealed the main theme as "Learning together through a relational and practical routine" and four sub‐themes. Conclusion: Men's Shed intergenerational mentoring programs present an environment for older, retired men to express generativity, improve their mental health and bond with younger generations.So what? The potential wellbeing implications for older men through intergenerational mentoring should form the basis of future research and intervention.